(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Uterine torsion is rare obstetrical complication up till 1992. Only 212 cases have been reported in literature. Here we present a case of 26 years old lady with history of previous II LSCS. She was 38 weeks pregnant with abruptio placenta + IUD baby. On opening the abdomen, she had Dextro rotation of uterus through an angle of 180. Baby was delivered through classical posterior uterine wall incision. Dextro rotation was corrected. Bilateral tubal ligation was done.